Anesthetic Management of Non-Cardiac Surgery in A Patient With Chemotherapy-Induced Cardiomyopathy and Severely Reduced Ejection Fraction: A Case Report - Dino Irawan; Mhd. Ayyub Rizki (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2026)
Chemotherapy-induced cardiomyopathy is a serious complication of cancer therapy that can lead to a significant reduction in left ventricular ejection fraction and increase the risk of perioperative morbidity and mortality in non-cardiac surgery. This study aims to describe the anesthetic management of a patient with severe ventricular dysfunction secondary to chemotherapy undergoing non-cardiac surgery. This study used a descriptive observational design in the form of a single case report with retrospective data collection through medical record review, including preoperative evaluation, supporting examination results, intraoperative anesthetic strategies, hemodynamic parameters, use of vasoactive drugs, and postoperative outcomes. Data were analyzed descriptively by comparing clinical findings with relevant literature. The results showed that an individualized anesthetic approach, selection of agents with minimal myocardial depressant effects, careful fluid management, and strict hemodynamic monitoring were able to maintain perioperative stability without major cardiovascular complications. This report emphasizes the importance of a risk-based anesthetic strategy in improving patient safety in individuals with severely reduced ejection fraction due to chemotherapy-related cardiotoxicity.